The Relationship between the Intensity of Participating Majelis Taklim and the Level of Religious Knowledge of the Community in Andilan Pasaman District - Marfalak, Marfalak; Solfema, Solfema (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
This research is motivated by the low level of religious knowledge among the Andilan community in Pasaman Regency, allegedly caused by several factors, one of which is the intensity of participating in "majelis taklim" (religious study gatherings) at Pusaka Mosque in Andilan, Pasaman Regency. This study aims to understand the description of the intensity of participating in "majelis taklim," assess the level of religious knowledge among the community, and determine the relationship between the intensity of participating in "majelis taklim" and the level of religious knowledge among the community in Andilan, Pasaman Regency. The research employs a quantitative approach with a correlational design. The study uses a sample of 80%, or 32 members of the "majelis," out of a total population of 42 members, selected through random sampling technique. Data collection tools include questionnaires and closed tests. The results of this study indicate that (1) the intensity of participating in "majelis taklim" in Andilan, Pasaman Regency, is classified as low; (2) the level of religious knowledge among the community participating in "majelis taklim" in Andilan, Pasaman Regency, is categorized as low; and (3) there is a positive and significant relationship between the intensity of participating in "majelis taklim" and the level of religious knowledge among the community in Andilan, Pasaman Regency.